ROLE OF INTERNAL AUDIT ON RURAL BANKS’ FINANCIAL AND NON-FINANCIAL PERFORMANCE - Candy Candy (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
This research aims to examine the effect of internal audit function on rural bank financial and non-financial performance. Data collection uses both primary and secondary data. Internal audit function and non-financial performance use questionnaires and 63 data were collected from 38 rural banks in Riau Islands Province. The financial performance uses return on asset (ROA) and return on equity (ROE) using the financial report published by Financial Services Authority of Indonesia. The respondents of this research are the director of rural banks. The analysis method uses Partial Least Square (PLS) to examine the outer and inner model. The result shows that the internal audit function positively affects both financial and non-financial performance. The rural bank, which has an established internal audit function, enhances the performance.